Together, somehow : music, affect, and intimacy on the dancefloor - García-Mispireta, Luis Manuel, 1978- (Duke University Press, 2023)
"Together, Somehow is Luis-Manuel Garcia Mispireta's exploration of "minimal" house and techno parties in Chicago, Paris, and Berlin during the early 2000s. In particular, Garcia Mispireta is interested in the utopic vision of the inclusive dancefloor, and the way that is produced through what he calls stranger-intimacy--the kind of warmth, sharing, and vulnerability between strangers that happens surprisingly often at popular electronic dance music parties. Drawing on fieldwork conducted in these cities, Together, Somehow rethinks intimacy and belonging through dancing crowds and throbbing dancefloors"--